Do Meetings in Smoke‐Filled Rooms Facilitate Collusion? - McCutcheon, Barbara (Journal of Political Economy, 1997)
The Sherman Act prohibits firms from discussing prices in meetings. Traditional thought suggests that this prohibition makes it harder for firms to collude, and economists have concluded that the Sherman Act operates in the public interest. I provide an alternative explanation for the act that also accounts for the small sanctions chosen by the legislature. When firms interact in a dynamic environment in which the law helps them to prevent renegotiation, the firms may benefit from the law that makes it costly, but not very costly, to meet to discuss prices. The Sherman Act may help firms to collude.